Effects of Late Summer Prescribed Fire on Botanical Composition, Soil Cover, and Forage Production in Caucasian Bluestem-Infested Rangeland in the Kansas Smoky Hills: Year 3 of 4 - M. P. Ramirez; A. J. Tajchman; Z. M. Duncan; J. Lemmon; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective was to document the effects of late-summer prescribed fire on soil cover, botanical composition, and forage production in the Kansas Smoky Hills and associated effects on dense Caucasian bluestem (Bothriochloa bladhii) stands therein. Study Description:The study took place on a private ranch in Ellsworth County, in the Kansas Smoky Hills. Eighteen one-acre plots were assigned randomly to one of two prescribed-fire treatments: no burn (control) and burn (burned August 14, 2019). Soil cover, plant composition, and forage production were evaluated annually. These data represent plant community effects prior to treatment and one and two years subsequent to treatment. The Bottom Line:These data were interpreted to indicate that one application of late-summer prescribed fire was associated with decreased presence of Caucasian bluestem and intermittent increases in native grass and forb richness, a component of biological diversity. Some declines in forage production were noted.
Keywords: botanical composition; old-world bluestems; prescribed burning